Child bride and forced marriages: Legal aspects - Clara Pettoello-Mantovani (Elsevier, 2024)
Abstarct: The scourge of underage marriages and forced unions transcends borders, impacting individuals under 18 across diverse regions, cultures, and religious beliefs, albeit with varying degrees of prevalence. Currently, one in every five girls globally becomes a bride before turning 18, with a staggering one-third wed before reaching 15. These unions exact a profound toll on emotional and social development, often depriving girls of their right to education, familial connections, leisure, and thrusting them into adult roles, including involuntary motherhood. The denial of childhood, coupled with the grave physical and emotional toll of underage and coerced marriages, yields lasting ramifications on girls' health, prospects, and overall well-being, imperiling not just their lives but also those of their offspring and the collective future. Such marriages constitute a severe form of child abuse, exposing girls to diverse forms of physical violence with enduring repercussions. This commentary, aims to heighten awareness among main stakeholders entrusted with the welfare of minors, including legislators, healthcare professionals and local communities, regarding this issue and its lasting perils. Finally, it underscores the pivotal role pediatricians can play as advocates, actively engaging in programs aimed at monitoring and thwarting the adverse personal and societal repercussions engendered by these distressing phenomena among the under-18 demographic.